Research on invulnerability of scale-free network with a unified method. (25th March 2019) - Li, Kaiju; Wang, Hao
Research on the invulnerability of scale-free network has outstanding benefit on building robust social, biological and technological networks in real world. Intuitively, prior studies attempt to investigate this topic under different conditions, including node/edge attack with or without cost, and get many valuable conclusions. However, current methods just evaluate the invulnerability from a single viewpoint, and lack a comprehensive description of this performance. Therefore, this paper proposes a unified framework to explore the invulnerability of scale-free network. Specifically, by exploring the transformation relations among node, edge and attack cost, we define a weight parameter t to unify the four cases, e.g., node/edge attack with or without cost. By this means, we can analyse the invulnerability from a comprehensive perspective rather than a single perspective. Furthermore, we re-analyse the invulnerability of scale-free network using our unified method and investigate the relationships among current research conclusions. Theoretical analysis and experimental results show that current conclusions are the cases corresponding to the specific values of t, and our method obtains other useful invulnerability conclusions with current methods.